A 1‐Year Prospective Clinical and Radiographic Study of Early‐Loaded Bone Level Implants in the Posterior Maxilla. (27th January 2014) - Marković, Aleksa; Čolić, Snježana; Šćepanović, Miodrag; Mišić, Tijana; Ðinić, Ana; Bhusal, Dinesh Sharma
Abstract: Purposes: The primary aim of the study was to investigate a 1‐year success rate of early‐loaded bone level implants with a chemically modified sand‐blasted, large grit, acid‐etched surface (SLActive®, Institut Straumann AG, Basel, Switzerland) in the posterior maxilla. Secondary objectives included stability of these implants and peri‐implant bone level. Materials and Methods: Bone level® implants (Institut Straumann AG) inserted into premolar and/or molar maxillary sites were loaded after 6 weeks of healing. The implants were monitored for 1 year using the following outcome measures: implant success, primary and secondary stability, and peri‐implant bone level. Results: Out of 37 implants placed in 13 patients, 36 reached sufficient stability and were early loaded, whereas one underwent a delayed loading protocol. One‐year success rate of early‐loaded implants was 100%. Implant stability at baseline was 71.7 ± 5. 6 to be steadily increased thereafter up to 1 year (80.3 ± 3.3), except at 2 weeks when a nonsignificant decrease was noticed (71.9 ± 3.9). Continuous and significant bone loss was observed, reaching 0.4 ± 0.1 mm in the first postoperative year. Conclusion: Bone level implants with the SLActive surface placed into low‐density bone and loaded after 6 weeks of healing can predictably achieve and maintain a successful tissue integration.